Association between Insulin Resistance and Breast Carcinoma: A Systematic Review and Meta-Analysis - Hernández, Adrian V. (2014)
This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.